Environmental resource guide on CD-ROM includes 1997 and 1998 updates - American Institute of Architects (New York : John Wiley, 1999)
Contains current information on the environmental aspects of building materials, based on a life-cycle analysis of materials.
Περιέχει βιβλιογραφία και ευρετήριο.
Απαιτήσεις συστήματος για Windows: Windows 3.1 and later or Windows 95; 8MB RAM for Acrobat Reader; Windows NT 3.5.1 or later; 16MB RAM for Acrobat Reader; Solaris 2.3, 2.4, or 2.5 operating system, 12MB of available hard space.
Απαιτήσεις συστήματος για Macintosh: 68020-68040; 3.5MB RAM available for Acrobat Reader; Power Macintosh 5MB RAM available for Acrobat Reader; Sun OS 4.1.3 or later, or Solaris 2.3, 2.4, or 2.5 operating system; 12MB of available hard space.
Keywords: Architecture -- Environmental aspects; Building materials -- Environmental aspects